Strategi Personal Branding Dedi Mulyadi Sebagai Tokoh Politik Humanis Di Akun Instagram @dedimulyadi71 - Hilda Badriyah; Detya Wiryani; Ahmad Taufiq Maulana Ramdan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Abstract Personal branding strategy of Dedi Mulyadi as a humanist political figure on Instagram @dedimulyadi71 This study analyzes how Dedi Mulyadi uses Instagram to build a humanist political image through consistent visual storytelling, cultural symbols, and direct social engagement. Using a qualitative descriptive method with an interpretative approach, data were gathered from Instagram content analysis and in-depth interviews with followers. Findings reveal that Mulyadi’s empathetic and grounded communication style fosters public trust and reshapes perceptions of political leadership. His strategy highlights the power of authentic narratives in digital political branding. This research contributes to political communication studies and offers practical insights for politicians navigating social media platforms. Keywords: Personal Branding, Humanist Politics, Digital Communication, Political Narative